2007
DOI: 10.1111/j.1439-0434.2007.01236.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of the 3′‐Terminal Region ofTurnip mosaic virusIsolates from Eastern China

Abstract: Turnip mosaic virus (TuMV; genus Potyvirus, family Potyviridae) causes great losses to cruciferous crop production worldwide. The 3¢-terminal genomic sequences of eight TuMV isolates from eastern China were compared with those of 74 other Chinese TuMV isolates of known host origin in the GenBank and isolated during the past 25 years. The reported sequences of the eight TuMV isolates are 1125 or 1126-nucleotides (nt) long excluding the poly(A) tail. They all contain one partial open reading frame of 912 nt, enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…Our previous results had shown that, according to the CP genes, Chinese TuMV isolates were under negative or purifying selection [21]. In this research, we confirmed that conclusion according to analyses of the whole ORF and other genes, and further proved that the selection pressure on P1, the most diverse part in potyviral genome, was the highest.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our previous results had shown that, according to the CP genes, Chinese TuMV isolates were under negative or purifying selection [21]. In this research, we confirmed that conclusion according to analyses of the whole ORF and other genes, and further proved that the selection pressure on P1, the most diverse part in potyviral genome, was the highest.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that, as the case for CP genes [21], the d NS / d S ratios for other genes were close to 0, which implied that negative or purifying selection on Chinese TuMV isolates. The d NS /d S ratios for genes P1 and P3 were higher than those for other genes, implying that the selection pressure on these two genes was higher.…”
Section: Diversity Of Chinese Tumv Isolates At Complete Genomic Levelmentioning
confidence: 88%
See 3 more Smart Citations